Pemanfaatan Tepung Biji Labu Kuning Dalam Pembuatan Pie Susu Sebagai Alternatif Camilan Sumber Zink - Iswahyudi Iswahyudi; Selva Mahlinasha Arindani; Izna Nurdianty Muhdar (Jurnal Teknologi dan Industri Pertanian Indonesia, 2023)
The purpose of this study was to examine the chemical and organoleptic properties of milk pie substituted with pumpkin seed flour as a snack SOURCE of zinc. This study used a completely randomized design (CRD) with 1 factor and 2 replications. The factor in this study was the addition of pumpkin seed flour as a substitute for wheat flour which consisted of 3 levels, namely F1 (50% : 50%), F2 (40% : 60%), F3 (30% : 70%), and F0 (100% : 0%) as control. Analysis of physical and chemical properties includes water content, ash content, protein content, fat content, carbohydrate content, total energy, and zinc content. The best milk pie formula was selected based on the hedonic test and the hedonic quality test using 50 untrained panelists. The results showed that the addition of pumpkin seed flour as a substitute for wheat flour in milk pie formulation had a significant effect on ash content (p=0,000), fat (p=0,000), carbohydrates (p=0,000), zinc (p=0,000), and energy total (p=0,001). The results hedonic and hedonic quality test showed that the addition of pumpkin seed flour as a substitute for wheat flour in milk pie formulation had a significant effect on hedonic texture (p=0,005), hedonic color (p=0,000), hedonic taste (p=0,002), overall (p=0,022), quality of texture (p=0,003), and quality of color (p=0,000). F1 (50% : 50%) become the selected milk pie formula with nutritional content per 100 g, 454 kcal energy, 11 g protein, 25,8 g fat, 44,3 g carbohydrate, and 2,05 mg zinc. The nutritional content of selected milk pie in one serving size is 140 kcal of total energy, 3 g of protein, 8 g of total fat, 13 g of total carbohydrates, 7 g of sugar, and 4% of zinc from the RDA.